POTENTIAL HAZARD ANALYSIS PROFESSION RADIOGRAPHER AT DEMAK HOSPITAL - Rifki Arfianto; Diki Bima Prasetio; Bina Kurniawan (Universitas Muhammadiyah Semarang, 2017)
Background: Potential hazards and risks in the workplace is the result of work systems or work processes, the use of machinery, equipment and ingredients are sourced from the limitations of his work. From the results of preliminary observations at the Hospital of Pelita Anugerah Mranggen Demak, researchers found several cases of work-related accidents in Radiology which are not recorded during this time. This study aimed to describe the potential hazards and risk values OSH and provide recommendations on the control of hazards in accordance with the standards. Methods: This study is a qualitative research with cross sectional approach. Subjects in this study consisted of 6 people technologist as key informants, 1 Chamber Head and 1 Chief of Radiology as an informer of existing support. The research variables are potential hazards, risks and value of the profession radiologist.Results: Control of danger that has been done in Radiology not meet the standards. Hazard control physics obtained is done using film badge and hide behind the veil of coated lead every task and biological hazards by wearing a mask and handscoon which then wash your hands after handling patient. Conclusion: The danger of physical and biological control are performed at the Hospital Radiology Pelita Anugerah Mranggen Demak not meet the standards, while for chemical hazards and ergonomic hazard control has not been done.Keywords: Risk Value, potential hazards, profession radiologist